Beethoven's nephropathy and death: discussion paper. - Davies, P J (1993)
The autopsy description of Beethoven's nephropathy is so typical of renal papillary necrosis, that the diagnosis is as near to certain as is possible, in the absence of a histological examination. A review of the symptoms and clinical course of Beethoven's final illness is consistent with this diagnosis. It is proposed that the cause was an acute onset diabetes mellitus, complicating chronic pancreatitis. Beethoven's case appears to be the first report in the literature of an autopsy proven case of renal papillary necrosis.